Jawabanmu

2014-06-16T15:42:51+07:00
L i m     16    -     4       = L i m       16             -     4      
x⇒3  x²-2x-3      x - 3        x⇒3    (x-3)(x+1)        (x - 3)
                                     = L i m 16-4(x+1)   
                                        x⇒3  (x-3)(x+1)
                                     = L i m -4x + 12  
                                        x⇒3  (x-3)(x+1)
                                     = L i m -4(x - 3)
                                        x⇒3 (x-3)(x+1)
                                     = L i m   -4     
                                        x⇒3   x + 1
                                     = -4/4
                                     = - 1